APPLICATION OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE (TPS) ON MATHEMATICAL COMMUNICATION ABILITY - Andi Mulawakkan Firdaus (Universitas Negeri Makassar, 2019)
This research is a quasi-experimental study which aims to describe the effect of cooperative learning type Think Pair Share (TPS) on students' mathematical communication skills, and to find out the percentage of students' activeness in participating in learning and knowing students' positive responses to learning. The output that will be generated in this study is that students can be more active in the learning process, more active in solving mathematical problems, and can be more confident in expressing their answers in public so that after applying cooperative learning models the Think Pair Share (TPS) mathematical communication skills of students will be better. The research subjects were divided into 2 groups, namely the experimental group taught using the cooperative learning model Think Pair Share (TPS) type, and the control group taught using Conventional learning models. Each group is taught with the same frequency of meetings with the same material. The results of the study show that the application of the cooperative learning model Think Pair Share (TPS) influences students' mathematical communication skills